Tax reforms in Ghana - Robert Darko Osei; Peter Quartey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Ghana's tax reforms constitute the major policy instrument needed to accelerate growth and poverty reduction. Over the past two decades, the government has consistently spent more revenue than it is able to generate and the gap is often financed with foreign aid which has perpetuated the country's aid dependency. Two options can be explored to reduce the gap between government revenue and expenditure; generate more revenue or reduce government expenditure. Although the latter sounds reasonable, the government needs to spend more on key sectors like education, health and infrastructure if the country is to significantly reduce poverty. The critical issue has been how to generate the needed resources domestically, using tax instruments that are least harmful to the poor. This will obviously involve reforming the tax system to ensure efficiency by widening the tax net without necessarily increasing the tax rate. This paper provides an assessment of the changing structure of the tax system in Ghana over the last two decades and suggests ways to improve tax administration in the country.
Keywords: H2; I3; 330; tax reforms; poverty; Ghana; Steuerreform; Armut; Ghana